2012
DOI: 10.1007/s00339-012-6799-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of packaging concepts for high-power diode laser bars

Abstract: Double-side cooled high-power diode laser bars packaged by different techniques on different types of passive heat sinks are analyzed in terms of packaging-induced strain. Reference data from standard devices being singleside cooled only and packaged by conventional soft and hard soldering are also presented. Thermal profiling across the devices complements the results. The most suitable packaging architecture and technique for double-side cooled bars is identified. Measurements of the laser emission near fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Winterfeldt et al [35] used degree of polarization measurements to aid in the investigation of the factors limiting the lateral beam parameter of 9xx nm high-power broad-area lasers. Hempel et al [36] made measurements on high-power lasers and provided a comparison of strain measurements by photoluminescence, Raman, and DOP of electroluminescence. Matsui et al [37] used results from DOP measurements and finite elements simulations of strain in their investigations of tuneable VCSELs.…”
Section: Introductionmentioning
confidence: 99%
“…Winterfeldt et al [35] used degree of polarization measurements to aid in the investigation of the factors limiting the lateral beam parameter of 9xx nm high-power broad-area lasers. Hempel et al [36] made measurements on high-power lasers and provided a comparison of strain measurements by photoluminescence, Raman, and DOP of electroluminescence. Matsui et al [37] used results from DOP measurements and finite elements simulations of strain in their investigations of tuneable VCSELs.…”
Section: Introductionmentioning
confidence: 99%
“…[7]. Laser emitters in regions of appreciable shear have been shown to emit less power than emitters in the center of the chip, where the shear strain is zero or small [13][14][15][16][17][18]. This reduction in power for emitters in regions of appreciable shear strain can be explained by birefringence owing to the presence of shear strain [7,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous work has been analysis of the DOP of PL or electroluminescence [13,17,[27][28][29][30][31][32][33][34]. CL offers better spatial resolution than PL.…”
Section: Introductionmentioning
confidence: 99%
“…This understanding of the shear strain (ROP) in one coordinate system as the difference of the tensile components (DOP) in a rotated coordinate system provides an explanation of how the shear strain creates a birefringence at 45 deg. Hempel et al [11] analyzed packaginginduced strain using spectroscopic techniques. They concluded that for emitters near the ends of a bar there might be an additional effect, and this additional effect might be shear strain.…”
mentioning
confidence: 99%